PERAN PELATIHAN DAN PENGEMBANGAN DALAM MENINGKATAN KINERJA KARYAWAN (KAJIAN LITERATURE REVIEW MANAJEMEN SUMBER DAYA MANUSIA) - Albiuma Tabina; Dian Sudiantini, Indah Bayu Lestari, Nadia Fadhilatul Ummah, Putri Nasywa Syakira, Restu Gita Hanida (CV. Adiba Aisha Amira, 2024)
In a rapidly changing and competitive business environment, it is crucial for organizations to have skilled and productive employees. Effective training and development is one of the key factors that influence employee performance. This study aims to examine the role of training and development in improving employee performance through a literature review. The method used is qualitative descriptive with a literature study from various relevant journals and websites. The findings indicate that employee training and development can enhance performance, productivity, and adaptability to changes in the business environment. Furthermore, structured and continuous training has a positive effect on employee motivation and engagement.